Thermal Characteristics of Coconut Shells as Boiler Fuel - Muhamad Yulianto; Edy Hartulistiyoso; Leopold Oscar Nelwan; Sri Endah Agustina; Chandra Gupta (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Agricultural waste products, such as wood, rice husk, corn waste, and coconut shells, are abundantly available and can potentially be used as an energy source, particularly for direct combustion in boilers. Because coconut production increases every year, it would be useful to find an alternative use for coconut shells, which are a type of coconut waste. As coconut shells can be used as fuel in boilers, the aim of this study was to evaluate the thermal characteristics of coconut shells in this regard. This study used experimental results to evaluate the performance of a boiler when coconut shells were used as solid fuel. The variations in feed rate were 5, 7.5, and 10 kg/h, and the water flow rates varied between 1 litre per minute (lpm), 2 lpm, and 3 lpm. Temperature data were collected every second via data acquisition , and the mass flow rate of the flue gas was collected every 5 min using a pitot tube equation. One of the parameters evaluated in determining the success of coconut shells as boiler fuel is the thermal efficiency of the boiler. The results showed that the maximum thermal efficiency reached approximately 62.04%, and the maximum flue gas temperature was approximately 500 ℃ for a biomass mass flow rate of 7.5 kg/h. The maximum water temperature of the boiler was 99 ℃, which was reached at a minimum water flow rate of 1 lpm. The results showed that coconut shells are suitable for use as boiler fuel.